2020
DOI: 10.7150/jca.37017
|View full text |Cite
|
Sign up to set email alerts
|

The somatic mutation landscape of Chinese Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the fifth leading cause of cancer-related death in China. The incidence of Chinese CRC has increased dramatically with the changes of dietary and lifestyle. However, the genetic landscape of Chinese colorectal cancer mutation is still poorly understood. In this study, we have performed whole exome-sequencing analysis of 63 CRC cases. We found that Chinese CRC were hypermutated, which were enriched in ECM-receptor interaction, antigen processing and presentation, and focal adhesion. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
5
14
0
Order By: Relevance
“…Fc fragment of IgG-binding protein (FCGBP) may represent one such protein marker as its expression is low in some tumors, while high in others [ 2 4 ]. For example, expression of FCGBP is low in gallbladder cancer, in which it serves as a key regulator of tumor growth factor 1 (TGF-1)-induced epithelial-mesenchymal transition [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fc fragment of IgG-binding protein (FCGBP) may represent one such protein marker as its expression is low in some tumors, while high in others [ 2 4 ]. For example, expression of FCGBP is low in gallbladder cancer, in which it serves as a key regulator of tumor growth factor 1 (TGF-1)-induced epithelial-mesenchymal transition [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al performed whole exome-sequencing analysis of 63 CRC cases, and found that with the deficiency of FCGBP , CRC developed and showed worse survival rates. 17 At stage I or II CRC, FCGBP was reported to be positively associated with the prognosis of CRC. 18 Onstenk et al measured CTCs of liver metastasis in CRC patients and their primary tumor tissues and found that FCGBP was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Defective variants in POLD1 and POLE , essential genes in the BER pathway, are related to significantly higher mutational burden and malignancy through BER’s correlation to the MMR pathway ( 47 ). Co-mutations in the MMR and HRR pathways may also be related to hypermutated CRC with worse survival, via interruption of DNA binding and replication ( 48 ). Our study reveals that beyond each single DDR pathway mutations, the co-mutations and the number of mutated DDR pathways are also significantly related to post-operative survival, and the correlations were independent of other clinical traits.…”
Section: Discussionmentioning
confidence: 99%